1991
DOI: 10.1002/jor.1100090516
|View full text |Cite
|
Sign up to set email alerts
|

The biologic effects of implant materials

Abstract: The interaction between implant materials and the surrounding biological environment continues to be an area of intense research and clinical interest. This article presents the information presented in a symposium, held during the 36th Annual Meeting of the Orthopaedic Research Society, in which several important issues concerning the biologic effects of implant materials were discussed. These issues included the mechanisms by which implant materials are released to the surrounding tissues and the ways in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
10

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(89 citation statements)
references
References 61 publications
0
79
0
10
Order By: Relevance
“…Como o plasma permeia toda a câmara, os íons de nitrogênio ao atingir as paredes da câmara, podem causar a ejeção (sputtering) destes elementos. Estudos prévios comprovam que o cromo é citotóxico a diversos tipos de célula, em especial osteoblastos, cuja viabilidade e proliferação são afetadas e, consequentemente, a osseointegração torna-se um problema [34][35][36]. Íons de ferro também mostram toxicidade, quando em forma de detritos em implantes ósseos [37].…”
Section: Materiais E Métodosunclassified
“…Como o plasma permeia toda a câmara, os íons de nitrogênio ao atingir as paredes da câmara, podem causar a ejeção (sputtering) destes elementos. Estudos prévios comprovam que o cromo é citotóxico a diversos tipos de célula, em especial osteoblastos, cuja viabilidade e proliferação são afetadas e, consequentemente, a osseointegração torna-se um problema [34][35][36]. Íons de ferro também mostram toxicidade, quando em forma de detritos em implantes ósseos [37].…”
Section: Materiais E Métodosunclassified
“…The information for inert metal toxicity in humans arises from foreign-body carcinogenesis data related to metals used for implants, stainless steel, shrapnel, etc. (Brand and Brand, 1980;Brand, 1994;Galante et al, 1991). Ta metal is physiologically inert and has been used in metal implants in animals and humans for many years (Beliles et al, 1994) without observed biologic effects.…”
Section: -Signature Datementioning
confidence: 99%
“…In an effort to continuously improve prosthetic materials, cementless joint replacements have been tried. However, lytic reactions have occurred, suggesting that similar tissue reactions may occur in a variety of fragmented materials, including metals (7).…”
Section: Tb and Foreign-body Reactions In A Knee Prosthesismentioning
confidence: 99%